Interpretasi Objek Wisata di Taman Wisata Alam Cani Sirenreng, Kabupaten Bone - Risma Illa Maulany; Muhammad Fiqhi Rachman; Amran Achmad (PERENNIAL, 2018)
Cani Sirenreng Nature Tourism Park is located in the  Bone Regency  which is under managed of Bureau Agency of the Conservation of The Natural Resources of South Sulawesi. This research aims to develop materials for the purposes of the interpretation of natural attractions in Cani Sirenreng Nature Tourism Park. The tourism object of Cani Sirenreng Nature Tourism Park was studied based on block utilization. The tourism object interpreted are physical, biological (flora and fauna) and social-cultural around the park. The first track was the track to Baruttunge Waterfall which became the main object with a height of 70 m waterfall, which is formed on the three levels of waterfalls. The second track was  the track to Coppo Cempa which featuring rows of hills and panoramic sunrise or sunset. In the track of  Coppo Cempa, there were 27 species of birds found here including Sulawesi Serpent Eagle  and Rofous Wingged Buzzard which were protected under the regulation. Direct interaction with the community around and viewing direct harvesting of nira of sugar palm can also be done in this track. This information can be used as the interpretation material to visitors coming to Cani Sirenreng Nature Tourism ParkKey words: Nature Tourism Park; potential of nature tourism; track (interpretation) tourism.